Social Work Practice and Disability Communities An Intersectional Anti-Oppressive Approach - Slayter, Elspeth; Johnson, Lisa (Open textbook library., 2024)
Designed as a main textbook for social work courses at the bachelor’s and master’s level or for social work practitioners in the field, this work moves beyond a traditional medicalized and segregated approach (i.e., chapters organized around impairments) to the exploration of disability-specific populations, instead taking a more intersectional approach in discussing specific service areas and practice issues while weaving in stories about the lived experiences of disabled people with a range of social identities. These issues include parenting, mass incarceration, ableism, aging, and employment, among many others. A key goal of this book is to introduce an intersectionality-informed and critically culturally competent approach to anti-oppressive social work practice with disabled people, primarily in the United States. To do this, we present an innovative practice model for social workers to use in their work with disabled people and communities, which is incorporated throughout the book in a variety of practice considerations. The main themes woven throughout our practice model are intersectionality theory, critical cultural competence, and anti-oppressive practice.